South Caucasus in the Foregin Policy of the Russian Federation. Do Doctrinal Assumptions Translate into Reality? - Kardaś, Jarosław (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2016)
Russian policy in South Caucasus is not a fully effective policy, as Russia’s actions towards Armenia, Azerbaijan and Georgia are dominated by bilateral relations rather than a single, coherent strategy towards the region. The policy towards these countries also bears the hallmarks of an imperial policy, since it boils down to rewards (in the political, economic or military sphere) for cooperation, or punishments for any action against Russian interests. In addition to enhancing bilateral relations, Russia makes efforts (in accordance with documents issued by official bodies) to integrate the CIS area, of course including the Trans-Caucasus, under its leadership. But it comes up short in these efforts, because not all the Caucasus countries are interested in Russian-led economic integration (within the Eurasian Economic Union), or political and military integration (within CIS, CSTO).

Polityka Rosji na Kaukazie Południowym nie jest polityką w pełni efektywną, bowiem działania Rosji wobec Armenii, Azerbejdżanu i Gruzji są zdominowane przez relacje dwustronne, a nie poprzez jednolitą spójną strategię wobec regionu. Polityka wobec tych państw ma także znamiona polityki imperialnej, bowiem sprowadza się do ich nagradzania (czy to w sferze politycznej, gospodarczej czy militarnej) za współpracę, bądź też karania za wszelkie wystąpienia przeciwko interesom Rosji. Oprócz budowania stosunków dwustronnych Rosja podejmuje (w zgodności z dokumentami wydawanymi przez oficjalne ograny) działania integracyjne obszaru WNP, w tym i oczywiście Zakaukazia pod jej przywództwem. Na tym polu nie odnosi jednak wielkich sukcesów, bowiem nie wszystkie kraje kaukaskie są zainteresowane integracją gospodarczą (w ramach Euroazjatyckiej Unii Gospodarczej) czy polityczno-wojskową (w ramach WNP, OUBZ) pod przywództwem Rosji.
Kaukaz Południowy w polityce zagranicznej Federacji Rosyjskiej - czy założenia doktrynalne przekładają się na rzeczywistość?
Keywords: South Caucasus; Russian Federation; the foreign policy; Armenia; Azerbaijan; Georgia; Kaukaz Południowy; Federacja Rosyjska; polityka zagraniczna; Armenia; Azerbejdżan; Gruzja